Role of aspirin in primary prevention of cardiovascular disease - Patrono, C; Baigent, C (Springer Nature, 2019)
The benefits of aspirin therapy for the secondary prevention of cardiovascular disease clearly outweigh the risks of bleeding, and low-dose aspirin is uniformly recommended in this setting. However, no clear consensus exists about whether, and if so in whom, aspirin therapy is appropriate for the primary prevention of cardiovascular disease. Three trials of low-dose aspirin versus placebo in three populations at increased risk of myocardial infarction or ischaemic stroke in the absence of established cardiovascular disease were reported in 2018. The ASPREE trial in elderly people was terminated early for futility because aspirin had no effect on disability-free survival but significantly increased the risk of major haemorrhage and, unexpectedly, all-cause mortality. In the ASCEND trial in patients with diabetes mellitus and no evidence of vascular disease, aspirin significantly reduced serious vascular events but increased major bleeding. In the ARRIVE trial in people with multiple risk factors for cardiovascular disease, aspirin had no effect on major cardiovascular events but increased gastrointestinal bleeding. The aim of this Review is to place these new results in the context of previous evidence on aspirin for the primary prevention of cardiovascular disease and to appraise whether the new evidence is likely to enable the more targeted use of aspirin in particular individuals for whom the net benefit is both clinically worthwhile and statistically definite.